SAT0470 Myositis, often suspected, is actually rare in primary sjÖgren's syndrome: data from the french cohort assess. (12th June 2018) - Felten, R.; Seror, R.; Vittecoq, O.; Hachulla, E.; Perdriger, A.; Dieude, P.; Dubost, J.-J.; Fauchais, A.-L.; Guern, V.le; Larroche, C.; Dernis, E.; Guellec, D.; et al.
Abstract : Background: Myositis prevalence in primary Sjögren's syndrome (pSS) and whether it is associated with peculiar extra-muscular involvement and/or a biological profile is unknown. Objectives: To refine prevalence and characteristics of patients with pSS and myositis. Methods: In the national multicenter prospective cohort ASSESS (395 patients with pSS with a 5 year-prospective follow-up), patients with suspected myositis were identified. Their charts were reviewed and the patients were compared with the rest of the cohort. Results: Myositis was suspected in 38 patients (2 men, 36 women, 58 29–78 yr old) because of myalgia and/or exercise intolerance (n=38) along with high blood CK level (n=28). As compared with the rest of the cohort, they had higher patient-reported signs including pain VAS, dryness VAS and patient reported index ESSPRI (6.3 vs 5.3, p=0.007). In contrast, proportion of systemic involvements (76.3% vs 70.9%, p=0.57) and systemic disease activity measured by the ESSDAI, without taking the muscular domain into account (2 vs 3, p=0.93), were not different from patients without suspected myositis. Demographic characteristics and disease duration were also similar. Electromyographic recording and/or muscle histology performed in these 38 patients objective muscular involvement in only 4 patients (1% of the cohort). - Three patients were diagnosed with inclusion body myositis (sIBM). Accordingly, age at first sign was 49 years, 49–60 muscle disease had progressive onset as suggested by the 11 years 1–28 delay between first muscle sign and diagnosis. CK level was <1000 UI/L. Immunomodulatory drugs had no effect on myositis, even though methotrexate, IVIg and rituximab were most frequently given than in patient without myositis (respectively 50% vs 12.4%; 75% vs 1.8% and 75% vs 4.9%; p<0.0001). - One pSS patient with myositis was a 39 years old woman with polymyositis. She developed proximal muscle weakness, CK was 750UI/L and muscle biopsy found endomysial infiltrate. Muscle force and CK level normalised with immunomodulatory drugs. Compared to the rest of the cohort, patient with myositis had longer disease duration at inclusion (15 vs 5 year, p=0.01) and tended to be younger at pSS diagnosis (41.5 vs 53 year, p=0.07). They had more frequent history of systemic manifestations (100% vs 65.0%, p=0.011) but ESSDAI at baseline (2 vs 3, p=0.56) and the biological characteristics were not different from patients without myositis. In contrast with the patients with suspected but not confirmed myositis, patient-reported signs (i.e. fatigue, pain, dryness and ESSPRI score) were similar to patients without myositis. Conclusions: Myositis is frequently suspected in patients with pSS, especially when patients-reported signs are particularly disabling. Myositis occurs very infrequently (1% of the cohort), in patients with longer disease duration. sIBM was the most predominant subset of myositis in the present study. Disclosure of Interest: None declared